Autotrophic and Heterotrophic Denitrification for Simultaneous Removal of Nitrogen, Sulfur and Organic Matter - Huilinir-Curio, C; Montalvo-Martinez, S (Taylor and Francis Inc., 2016)
The aim of this investigation was to assess the startup and operation of a laboratory-scale hybrid UASB-Anaerobic Filter Reactor (UASFB) of 1 L volume, kept at 30°C, in order to carry out a simultaneous autotrophic and heterotrophic denitrification process. First, the heterotrophic and autotrophic populations were separately enriched, with specific cultures and subsequently the UASFB was inoculated with 2 g L−1 of volatile suspended solids (VSS), with a ratio of 1.5:1 (autotrophs: heterotrophs). The influent or synthetic wastewater used was composed of: Na2S2O3·5H2O, CH3COOK, NaNO3, NaHCO3, K2HPO4, NH4Cl and saline solution. The concentrations varied depending on the organic loading rate (OLR), nitrogen loading rate (NLR) and sulfur loading rate (SLR) applied. In the UASFB reactor, two experimental conditions were tested and assessed: (i) COD/N ratio of 3.6 and SLR of 0.75 kg S m−3 d−1; and (ii) COD/N ratio of 5.8 and SLR of 0.25 kg S m−3 d−1. The results obtained demonstrated that an inoculum coming from an anaerobic reactor was able to carry out the process, obtaining a maximum nitrate removal of 85.3% in the first stage of operation and 99.5% in the second stage. The recovery of sulfur in form of sulfate in the effluent did not present a tendency to stabilize during the measured time, with a maximum thiosulfate removal of 32.5%, when the SLR was lowered to 0.25 kg S m−3 d−1. The maximum organic matter elimination, measured as COD, was 75.8%, which indicates the relatively good performance and behavior of the heterotrophic microorganisms. © 2016 Taylor & Francis Group, LLC.